2015
DOI: 10.1371/journal.pone.0140501
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of Individual Differences in Subjective Responses to D-Amphetamine, Alcohol, and Delta-9-Tetrahydrocannabinol Using a Within-Subjects Randomized Trial

Abstract: Polydrug use is common, and might occur because certain individuals experience positive effects from several different drugs during early stages of use. This study examined individual differences in subjective responses to single oral doses of d-amphetamine, alcohol, and delta-9-tetrahydrocannabinol (THC) in healthy social drinkers. Each of these drugs produces feelings of well-being in at least some individuals, and we hypothesized that subjective responses to these drugs would be positively correlated. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 61 publications
1
10
0
2
Order By: Relevance
“…One study demonstrated a greater increase in cannabis-induced “high” in female cannabis users compared to males [122], yet another study in non-users exposed to cannabis reported greater increases in “high” ratings in males compared to females [123]. Conflicting evidence may be due to smoking status differences in the populations of each study, as well as differences in THC capsule dosing indicated in each experimental design.…”
Section: Sex Differences In the Rewarding Properties Of Cannabinoidsmentioning
confidence: 99%
“…One study demonstrated a greater increase in cannabis-induced “high” in female cannabis users compared to males [122], yet another study in non-users exposed to cannabis reported greater increases in “high” ratings in males compared to females [123]. Conflicting evidence may be due to smoking status differences in the populations of each study, as well as differences in THC capsule dosing indicated in each experimental design.…”
Section: Sex Differences In the Rewarding Properties Of Cannabinoidsmentioning
confidence: 99%
“…At the same time, relatively higher amounts found in Bedrocan ® -MCT deserve further study as it was demonstrated that this heptyl Δ 9 -THC homologous showed a cannabimimetic activity several times higher than Δ 9 -THC, both under in vitro and in vivo conditions [ 8 ]. The discovery of this extremely potent Δ 9 -THC-like phytocannabinoid in both the Bedrocan ® and Bediol ® chemotype may explain several pharmacological effects not attributable exclusively to Δ 9 -THC [ 37 ]. The results of this study, although preliminary, indicate that in deep investigation toward the presence of untarget cannabonoid, such as Δ 9 -THCP, would be strategic, in order to characterize the different cannabis chemotypes involved in disease treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated in animals and humans that THC has differential effects in males and females. 70 Sex differences have been observed in the pharmacokinetics, [71][72][73][74] pharmacodynamics, [75][76][77][78] subjective effects, [79][80][81][82] abuse liability, [83][84][85][86] and therapeutic potential of THC (for recent review see Cooper and Craft 70 ). Thus, other agents that target the endocannabinoid system, such as CBD, might be expected to have similar sex-dependent effects.…”
Section: Sex Differences In Anxiety and The Utility Of Cbdmentioning
confidence: 99%